2019
DOI: 10.4236/ojtr.2019.72004
|View full text |Cite
|
Sign up to set email alerts
|

The Psychosocial Impact and Value of Participating in a Storytelling Intervention for Patients Diagnosed with Cancer: An Integrative Review

Abstract: Background: Interventions have recently been developed to test the therapeutic value of storytelling for people with cancer. This evidence includes different designs, as a result an integrative review is needed that can determine the impact and value of storytelling interventions for people with cancer. Aims: To undertake an integrative review of evidence identifying the impact and outcomes from storytelling interventions for people with cancer. Methods: An integrative review of group based storytelling interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…Where no behavior change was reported, the benefit appeared to be on a participant’s psycho-emotional well-being. This has been identified in other studies, e.g., [28].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Where no behavior change was reported, the benefit appeared to be on a participant’s psycho-emotional well-being. This has been identified in other studies, e.g., [28].…”
Section: Discussionsupporting
confidence: 83%
“…Review evidence has identified a lack of studies that use story telling for people with PD [36]. In other populations, storytelling interventions have been associated with encouraging positive attitudes and behaviors, such as physical activity and dietary changes [28,37]. This current study supports these findings for people with PD.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This encompasses the three sub-themes: Social (S), Internal (I) and Physical (P) factors which influence acceptance and risk taking. (a) Social support (S) within the community and family settings should be encouraged, as should access to others who have taken risks through storytelling intervention [47]. Family support may facilitate safe, achievable activities into the daily routine to increase independence [32].…”
Section: Discussionmentioning
confidence: 99%
“…Sharing and using illness narratives may be one way to develop the therapeutic relationship between people with H&NC and HCPs [21]. Illness narratives are stories that are expressed by individuals that allow the person to make sense of their experience.…”
Section: Introductionmentioning
confidence: 99%